2016
DOI: 10.1002/ppap.201600163
|View full text |Cite
|
Sign up to set email alerts
|

Generation of non‐equilibrium condition in solution plasma discharge using low‐pass filter circuit

Abstract: Solution plasma process has been researched as one of the synthetic methods of nano‐ and functional materials using plasma discharge in liquids. In this study, a low‐pass filter circuit was introduced to increase the density and temperature of electrons involved in a non‐equilibrium condition. The discharge properties of the solution plasma generated by conventional and low‐pass filter circuits were characterized and comparatively analyzed. Filtration of the MHz range current oscillations, an increase in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…From the electrical measurements, the input energy per pulse, the total energy of SPP during the total processing time, the auxiliary timedependent voltage, and the current oscillations of plasma that strongly influence the materials can be evaluated. 21) The electrical discharges in water produce chemically active species, such as hydrogen, hydrogen peroxide, ozone, oxygen, hydroxyl radicals, and photons as UV radiation, which dissociate molecules at a high efficiency. 22) Different types of discharges in water under high pulsed voltage with various pulse widths and repetition frequencies, and different electrode configurations arranged in a rod-plate 8,[23][24][25] or twopin 26,27) configurations have been investigated.…”
Section: Spp Diagnosticsmentioning
confidence: 99%
“…From the electrical measurements, the input energy per pulse, the total energy of SPP during the total processing time, the auxiliary timedependent voltage, and the current oscillations of plasma that strongly influence the materials can be evaluated. 21) The electrical discharges in water produce chemically active species, such as hydrogen, hydrogen peroxide, ozone, oxygen, hydroxyl radicals, and photons as UV radiation, which dissociate molecules at a high efficiency. 22) Different types of discharges in water under high pulsed voltage with various pulse widths and repetition frequencies, and different electrode configurations arranged in a rod-plate 8,[23][24][25] or twopin 26,27) configurations have been investigated.…”
Section: Spp Diagnosticsmentioning
confidence: 99%
“…The electrical breakdown can be controlled by the injection of more electrons into the ionization field in the bubble. Heo et al revealed the current-voltage waveform by low-pass filter circuits, which could reduce noise signals as compared to that of the conventional circuits when the bipolar pulsed voltage was applied [ 45 ]. The stages of the applied voltages, breakdown, and plasma generation in the solution plasma process are also proposed in Figure 3 .…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 99%
“… Schematic diagrams of the applied voltage, breakdown, and plasma generation stages in the SPP with the background of the current and voltage waveforms obtained by low-pass filter circuits [ 45 ]. …”
Section: Figurementioning
confidence: 99%